Analisa Tegangan Maksimum Pada Desain Struktur Mesin Pengering Bekatul dengan Tebal 0.7 mm dan Variasi Material Menggunakan Metode Elemen Hingga - Hendra Hendra; Dimas Maulana Putra; Dwinanto Dwinanto; Shofiatul Ula; Dhimas Satria; Mekro Permana Pinem; Mohamad Ana Syabana; Hamdan Akbar Notonegoro (Politeknik Negeri Padang, 2024)
Rice bran is one of the parts produced from rice milling, this part contains more than 20% dietary fiber. Rice bran has many useful substances, but its use is hampered by bran itself because it is easily damaged due to hydrolytic and oxidative activity. To overcome this problem, another method is needed so that the Bekatul can last longer. A drying machine is a machine used to reduce the air content in a substance. The aim of this research is to design the structure of a rice bran drying machine with various types of selected materials to obtain stress and cooling values. The method used in this research is finite element simulation. The materials varied in this research were AISI 304, Aluminum alloy 6061 and Galvalume Steel with thickness 0.7 mm. From the test results, it can be stated that all materials are safe to be used as the main material for making structure. However, there is one best material that produces the best maximum stress values and the smallest displacement, namely Galvalume Steel